Scanning and Governing: CONFEF recommendations for physical education in the school - Marcos Garcia Neira; Clayton Cesar de Oliveira Borges (Universidade Federal do Rio Grande do Sul, 2018)
Amid the dispute over conceptions for the teaching of Physical Education in schools, the Federal Council of Physical Education published a set of recommendations to be followed by all teachers. This article appeals to the order of Foucauldian matrix discourse to analyze the document, aiming to identify which perspective the document validates and what gaps it intends to fill. It is observed that the proposal results in an alchemy of curriculum theories, whose foundations are firmly rooted in the acritical pedagogies of Physical Education. The discursive production examined reproduces in a light and disjointed way obsolete teaching concepts and exalts the culture of performativity, based on the biological discourse of the healthy body. The regime of truth established by the official discourse gives way to a biopolitics with a view to the establishment of an active, productive and self-entrepreneur subject, meeting the expectations of the neoliberal society.